Analisis Semiotika Self-Love (Mencintai Diri Sendiri) dalam Video Klip “Jiwa yang Bersedih “ Ghea Indrawari - Herri Setiawan (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The purpose of this study is to apply self-love to help maintain mental health and reduce the risk of disorders in one's psychological condition in Ghea Indrawati's